MANAJEMEN PUBLIK HUMAS RELATION DALAM MENINGKATKAN MUTU MADRASAH - zuhriatin zuhriatin zuhriatin (VICRATINA, 2018)
This paper presents about public relations public relations management in improving the quality of madrassas. Madrasah is one of the most important Islamic educational institutions in Indonesia. The existence of madrassas is so important in creating the generation of a nation with insightful Islam. To achieve this goal of course a madrasah can not be separated from a management term, which management is a container of a planning. Not only the necessary management of cooperation of related components is also very important, the only by realizing a harmonious communication ties between schools and surrounding communities. With this expected the community is able to support and want to cooperate on what has become the goal of a predetermined plan.